Temporal study of arboviroses: A space analysis (Research, Society and Development, 2021)
The objective of the study is to analyze spatially the temporal distribution of the reported cases of Arboviroses in the 167 municipalities of Rio Grande do Norte, in the last 10 years. This is a quantitative, ecological, descriptive, cross-sectional study, analyzing spatially the Arboviroses Dengue, Zika and Chikungunya. Secondary data were available in the SUS-DATASUS Computing Program, and data provided by the Public Health Secretariat of Rio Grande do Norte-SESAP. The research was composed of the reported cases of Arbovirosis in the population of Rio Grande do Norte from 2007 to 2016. The data were tabulated in the Excel version 2013 program and later migrated to organization and statistical analysis in the SPSS version 22 program. Spatialization was performed in the TABWIN version 32 program. Dengue presents the highest Arbovirose in 2016, with the highest number of notifications in the seventh state health region, and a rapid spread of Zika and Chikungunya in the last three years. In the spatial analysis, the distribution is differentiated depending on the prevalence rate of Arbovirose, with Dengue and Chikungunya highlighting municipalities in the region of Seridó (fourth region) and Zika in Trairi, more precisely in the fifth region. It is concluded that greater evaluations by epidemiological surveillance are necessary in the regions with the highest prevalence of Arbovirosis in the State, in order to strengthen and redirect policies to control these diseases and with that, to draw up better preventive and educational strategies directed to these diseases.